Bronchoscopic Lung Volume Reduction - Ernst, Armin; Anantham, Devanand (Pulmonary Medicine, 2011)
The application of lung volume reduction surgery in clinical practice is limited by high postoperative morbidity and stringent selection criteria. This has been the impetus for the development of bronchoscopic approaches to lung volume reduction. A range of different techniques such as endobronchial blockers, airway bypass, endobronchial valves, thermal vapor ablation, biological sealants, and airway implants have been employed on both homogeneous as well as heterogeneous emphysema. The currently available data on efficacy of bronchoscopic lung volume reduction are not conclusive and subjective benefit in dyspnoea scores is a more frequent finding than improvements on spirometry or exercise tolerance. Safety data are more promising with rare procedure-related mortality, few serious complications, and short hospital length of stay. The field of bronchoscopic lung volume reduction continues to evolve as ongoing prospective randomized trials build on earlier feasibility data to clarify the true efficacy of such techniques.